The first pterosaur basihyal, shedding light on the evolution and function of pterosaur hyoid apparatuses - Shunxing Jiang; Zhiheng Li; Xin Cheng; Xiaolin Wang (PeerJ, 2020)
The pterosaur is the first known vertebrate clade to achieve powered flight. Its hyoid apparatus shows a simplification similar to that of birds, although samples of the apparatus are rare, limiting the ability to make an accurate determination. In this study we reveal a new pterosaur specimen, including the first definite basihyal. Through the comparison of pterosaur hyoids, a trend has been discovered for the shortened hyoid relative to the length of the skull, indicating a diminished role of lingual retraction during the evolution of the pterosaur. The new material, possibly from a gallodactylid Gladocephaloideus, represents one of the least effective lingual retractions in all pterosaurs. Based on the structure of an elongated ceratobranchial and retroarticular process on mandibles, the function of the Y-shaped istiodactylid tongue bone is similar to those of scavenger crows rather than chameleons, which is consistent with the interpretation of the scavenging behavior of this taxon. More fossil samples are needed for further study on the function of other pterosaur hyoids.